Analisis Melodi Dan Syair Pada Buku Ende. No. 512. “Didalani Jesus Tano Dohot Laut” Di HKBP Sisordak Resort Simamora - Lasmaria Purba; Diana Situmeang; Testi Bazarni Zebua (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2023)
The aim of this research is to analyze the melody of the song and analyze the lyrics of the song Buku Ende Number 512.